Analisis CAMEL untuk menilai tingkat kesehatan perusahaan perbankan yang terdaftar di Bursa Efek Indonesia - Novitasari, Ririn; Yuliati, Anik (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the soundness of banking companies listed on the Indonesia Stock Exchange in 2016–2020. Assessment of bank health is very important because it forms trust in the banking world. Measuring the soundness of a bank can be done using the CAMEL approach, namely the analysis of the factors of capital (capital), asset quality (asset quality), management (management), earnings (profitability), liquidity (liquidity). This is an official measuring instrument that has been set by Bank Indonesia to calculate the health of banks in Indonesia. This study uses descriptive quantitative research methods to describe and analyze the data or numbers contained in the financial statements of general banking companies listed on the IDX, consisting of financial statements for the 2016–2020 period. The sample for this research was taken using the purposive sampling technique. The data analysis technique in this study uses SPSS 25 application software. The results of this study prove that the net profit margin (NPM) has an effect on the bank's soundness level. Meanwhile, the capital adequacy ratio (CAR), non-performing loan (NPL), return of assets (ROA), operating expenses to operating income (BOPO), and loan to deposit ratio (LDR) have no effect on bank soundness level.